2009
DOI: 10.1002/cbdv.200800122
|View full text |Cite
|
Sign up to set email alerts
|

Catechin and Catechin Fractions as Biochemical Markers to Study the Diversity of Indian Tea (Camellia sinensis (L.) O. Kuntze) Germplasm

Abstract: The heterogeneous Indian tea germplasm includes 'China', 'Assam', 'Cambod', and their hybrids which were evaluated using biochemical markers viz., total catechin and their fractions, for varietal identification and characterization. Principal component analysis (PCA) of biochemical characters showed that the total catechin and trihydroxylated catechin has higher eigenvalues. The first two principal components (PCs) could differentiate more than 90% of the clones studied. This grouping based on first two princi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Chen and Zhou (2005) reported a large variation of TC content over 596 accessions of tea genetic resources, preserved in the China National Germplasm Tea Repository. Meanwhile, Gulati et al (2009) proposed the biochemical characterisation with different proportion of TC and its components would be a useful tool in the development of quality-tea clones. However, in this study, differences among locations were far larger than variation among cultivars, implying the environmental effect should be taken into consideration when TC and its component contents are utilised as biochemical markers in a tea breeding program (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen and Zhou (2005) reported a large variation of TC content over 596 accessions of tea genetic resources, preserved in the China National Germplasm Tea Repository. Meanwhile, Gulati et al (2009) proposed the biochemical characterisation with different proportion of TC and its components would be a useful tool in the development of quality-tea clones. However, in this study, differences among locations were far larger than variation among cultivars, implying the environmental effect should be taken into consideration when TC and its component contents are utilised as biochemical markers in a tea breeding program (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, catechin and its components have been widely utilised in studying the diversity of tea germplasm (Gulati et al, 2009;Magoma, Wachira, Obanda, Imbuga, & Agong, 2000). Catechins are considered to be synthesised through phenylpropanoid and flavonoid biosynthetic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulation of catechin has been found to differ the China, Assam, and Cambod cultivars. Catechin content has been reported to be lower in China types than in Assam and Cambod types (Takeda, 1994;Magoma et al, 2000;Gulati et al, 2009). Further, Iwasa (1977 reported that catechin content is higher in young leaves of var.…”
Section: Discussionmentioning
confidence: 99%
“…This fingerprinting will help to trace the origin of teas (Borse et al 2002). Catechin and its components had been widely utilized in studying the diversity of tea germplasm (Magoma et al 2000;Gulati et al 2009); yet, it was found that total catechin of tea leaves increased with the increase in sunlight exposure, suggest-ing that catechin biosynthesis was also dependent on the environment (Mariya et al 2003) and geographical location of a plant (Wei et al 2011).…”
Section: Biochemical Markersmentioning
confidence: 97%
“…The Indian tea germplasm comprising 'China', 'Assam', 'Cambod', and their hybrids, were evaluated using biochemical markers such as total catechins and their fractions for varietal identification and characterization of various made tea samples from northern India (Gulati et al 2009) as well as southern India (Saravanan et al 2005). Morphologically indistinct large-leaved 'Cambod' and 'Assam' varieties could not be differentiated using biochemical markers, since both varietal types taxonomically belong to a single species.…”
Section: Biochemical Markersmentioning
confidence: 99%